MODEL ELECTRONIC WORD OF MOUTH DAN KUALITAS PRODUK DALAM MENINGKATKAN KEPUTUSAN PEMBELIAN KONSUMEN DENGAN MEDIASI BRAND IMAGE PADA PRODUK DODOL PICNIC GARUT - Fahmi Dharmawan, - (2021)
The food industry of Dodol Picnic Garut plays a very important role for the regional economy. Along with the development of tourism in West Java today, which causes a multiplier effect, especially an increase in demand for special foods from the region. However, due to the Covid-19 Pandemic, sales decreased due to the PSBB policy which did not allow tourism spots to open normally. The dodol Picnic company is carrying out a strategy to use online sales through social media and digital platforms. Changes in the marketing strategy of dodol are currently also being carried out through social media and digital platforms which have the potential to affect the brand image so that consumers can decide to buy dodol picnic Garut products. Therefore, the purpose of this study is to determine the effect of electronic word of mouth, product quality, and brand image on purchasing decisions. This research was developed through a quantitative approach. The implementation of this study used a survey research design with a questionnaire as the instrument. The results of this study can explain that seven acceptable hypotheses, namely testing in this study confirms that there is a direct effect of e-WOM activity in increasing the brand image of the dodol picnic Garut products. Likewise, the influence of consumer activity in assessing product quality is good by consumers on dodol picnic Garut products. The influence of the consumer's brand image on the dodol picnic Garut products. Likewise, the influence of consumer judgment on product quality in dodol picnic Garut products, the consumer's purchasing decisions for dodol picnic Garut products are also increasing. This research also contributes to the increase in purchasing decisions dodol picnic Garut. If implemented properly, consumers will make many purchasing decisions so that they have an impact on improving business performance and maintaining their business amid the conditions of the Covid-19 Pandemic. The results of the author's research analyze that each of the research variables produces dimensions that are considered high in value, for that the authors assume that if the company will increase sales through social media and digital platforms, then the company must carry out the process of the arguments that the authors provide, including: need to be maintained e-WOM the role of concern for other consumers must be increased, the role of product quality needs to maintain the dimensions of product reliability, as well as for the brand image it is necessary to maintain the corporate image of consumers in order to remain good, and for purchasing decisions it is necessary to maintain and improve the dimensions of timing where and when the product is launched.